Palaeomagnetic analysis of plunging fold structures: Errors and a simple fold test - Stewart, Simon A. (Earth and planetary science letters, 1995)
The conventional corrections for bedding dip in palaeomagnetic studies involve either untilting about strike or about some inclined axis—the choice is usually governed by the perceived fold hinge orientation. While it has been recognised that untilting bedding about strike can be erroneous if the beds lie within plunging fold structures, there are several types of fold which have plunging hinges, but whose limbs have rotated about horizontal axes. Examples are interference structures and forced folds; restoration about inclined axes may be incorrect in these cases. The angular errors imposed upon palaeomagnetic lineation data via the wrong choice of rotation axis during unfolding are calculated here and presented for lineations in any orientation which could be associated with an upright, symmetrical fold. This extends to palaeomagnetic data previous analyses which were relevant to bedding-parallel lineations. This numerical analysis highlights the influence of various parameters which describe fold geometry and relative lineation orientation upon the angular error imparted to lineation data by the wrong unfolding method. The effect of each parameter is described, and the interaction of the parameters in producing the final error is discussed. Structural and palaeomagnetic data are cited from two field examples of fold structures which illustrate the alternative kinematic histories. Both are from thin-skinned thrust belts, but the data show that one is a true plunging fold, formed by rotation about its inclined hinge, whereas the other is an interference structure produced by rotation of the limbs about non-parallel horizontal axes. Since the angle between the palaeomagnetic lineations and the inclined fold hinge is equal on both limbs in the former type of structure, but varies from limb to limb in the latter, a simple test can be defined which uses palaeomagnetic lineation data to identify rotation axes and hence fold type. This test can use pre- or syn-folding lineations and could be useful in areas of non-coaxial folding.